Socio-demographic factor that impinge youth acceptance towards agriculture: the case of contract farming in Malaysia - Mohamed Shaffril, Hayrol Azril; D'Silva, Jeffrey Lawrence; Uli, Jegak; Abu Samah, Bahaman (International Digital Organization for Scientific Information, 2010)
Contract farming has been identified as one of the agriculture branches that have a huge potential to attract youth participation in agriculture based on its bigger profits and easiness to conduct. This study intends to investigate socio-demographic factor that affect acceptance towards contract farming among youth in Malaysia. A total of 400 respondents were involved in this study. The respondents were selected from four universities in Malaysia and all of them are either in Agriculture, Economic or other courses (social science and pure science). From the ANOVA test conducted it can be concluded that zone have significant difference with acceptance towards contract farming while Pearson Correlation employed indicates that age and monthly expenditure have no significant relationship with acceptance towards contract farming.